Laboratory evaluation of sample collection methods (organs vs swabs) for Tasmanian salmon reovirus detection in farmed Atlantic salmon, Salmo salar L. Issue 4 (5th November 2012) - Zainathan, S C; Carson, J; Crane, M St J; Nowak, B F
Abstract The use of swabs relative to organs as a sample collection method for the detection of Tasmanian salmon reovirus (TSRV) in farmed Tasmanian Atlantic salmon, Salmo salar L., was evaluated by RT‐qPCR. Evaluation of individual and pooled sample collection (organs vs swabs) was carried out to determine the sensitivity of the collection methods and the effect of pooling of samples for the detection of TSRV. Detection of TSRV in individual samples was as sensitive when organs were sampled compared to swabs, and in pooled samples, organs demonstrated a sensitivity of one 10‐fold dilution higher than sampling of pooled swabs. Storage of swabs at 4 °C for t = 24 h demonstrated results similar to those at t = 0. Advantages of using swabs as a preferred sample collection method for the detection of TSRV compared to organ samples are evident from these experimental trials.